Highly Porous Silicon Membranes Fabricated from Silicon Nitride/Silicon Stacks. Issue 14 (13th March 2014) - Qi, Chengzhu; Striemer, Christopher C.; Gaborski, Thomas R.; McGrath, James L.; Fauchet, Philippe M.
<x xml:space="preserve">Abstract</x> Nanopore formation in silicon films has previously been demonstrated using rapid thermal crystallization of ultrathin (15 nm) amorphous Si films sandwiched between nm‐thick SiO2 layers. In this work, the silicon dioxide barrier layers are replaced with silicon nitride, resulting in nanoporous silicon films with unprecedented pore density and novel morphology. Four different thin film stack systems including silicon nitride/silicon/silicon nitride (NSN), silicon dioxide/silicon/silicon nitride (OSN), silicon nitride/silicon/silicon dioxide (NSO), and silicon dioxide/silicon/silicon dioxide (OSO) are tested under different annealing temperatures. Generally the pore size, pore density, and porosity positively correlate with the annealing temperature for all four systems. The NSN system yields substantially higher porosity and pore density than the OSO system, with the OSN and NSO stack characteristics fallings between these extremes. The higher porosity of the Si membrane in the NSN stack is primarily due to the pore formation enhancement in the Si film. It is hypothesized that this could result from the interfacial energy difference between the silicon/silicon nitride and silicon/silicon dioxide, which influences the Si crystallization process.